Smart Queuing and Appointment Management System for Client Services in Bulacan State University Bustos Campus - Alaina Thea V. Concepcion; Anthony U. Concepcion; Clarisse Ann A. Guinto; Christian Araza; Rhye Dayrone H. Imperio; Beverly Regaas; Nino Marine N. Perez (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Client service efficiency has been a key issue in academic institutions as the rise in student populations overburdens the administrative functions of institutions. To eliminate the issues of manual queuing and appointment systems, this paper has developed the Smart Queuing and Appointment Management System, the web-based system that targets the administration of Bulacan State University -Bustos Campus. The system is expected to simplify the flow of clients, decrease waiting time and improve service delivery by using automated queue management, online scheduling and real time monitoring of transactions. The project was designed in HTML, CSS, JavaScript, PHP, and MySQL and adhered to the Agile Software Development Life Cycle (SDLC) to guarantee iterative user-driven enhancement of the project. To measure the performance and acceptability of the system, the Technology Acceptance Model (TAM) and the ISO/IEC 25010:2023 Software Quality Standards were used, and the techniques were functionality, usability, reliability, and efficiency. The evaluation involved 50 respondents, who were recorded in terms of surveys and interviews, and they were a combination of students, administrative staff, and IT specialists. The result showed that the system had a general weighted mean of 4.59 according to ISO/IEC 25010, which is interpreted as Strongly Agree, and this shows a high-quality functionality, reliability and usability. Under TAM, the responses of staff and students were very positive and the weighted means of responses were 4.84 and 4.45, respectively. These findings indicate that the system is successfully used to increase administrative efficiencies, reduce congestion as well as client satisfaction.